Axin2‐mTurquoise2: A novel reporter mouse model for the detection of canonical Wnt signalling. Issue 10 (19th September 2017) - de Roo, Jolanda. J. D.; Breukel, Cor; Chhatta, Amiet R.; Linssen, Margot M.; Vloemans, Sandra A.; Salvatori, Daniela; Mikkers, Harald M. M.; Verbeek, Sjef J.; Staal, Frank J.T.
Summary: The canonical Wnt signalling pathway has been implicated in organogenesis and self‐renewal of essentially all stem cell systems. In vivo reporter systems are crucial to assess the role of Wnt signalling in the biology and pathology of stem cell systems. We set out to develop a Turquoise (TQ) fluorescent protein based Wnt reporter. We used a CRISPR‐Cas9 approach to insert a TQ fluorescent protein encoding gene into the general Wnt target gene Axin2, thereby establishing a Wnt reporter mouse similar to previously generated Wnt reporter mice but with the mTurquoise2 gene instead of E. coli ‐β‐galactosidase ( LacZ ). The use of mTurquoise2 is especially important in organ systems in which cells need to a be alive for further experimentation such as in vitro activation or transplantation studies. We here report successful generation of Axin2‐TQ mice and show that cells from these mice faithfully respond to Wnt signals. High Wnt signals were detected in the intestinal crypts, a classical Wnt signalling site in vivo, and by flow cytometry in the thymus. These mice are an improved tool to further elucidate the role of Wnt signalling in vivo.